Effective and Efficient Organisations? Government Export Promotion in Germany and the UK from an Organisational Economics Perspective - Hauswirth, Iris A.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2006)
Using organisational economics theory, the author develops a conceptual framework for analysing the effectiveness and efficiency of public services delivery. In applying the framework to case studies of export support organisations in Germany and the UK , the research establishes the causal links between organisational structures and outputs. The decisive variables are knowledge and incentives of the actors, and adaptability of the organisation. Since there are trade-offs between the variables, the findings help to explain why one organisation may be different from, but equally effective and efficient as another, and why, despite ongoing re-structuring of public and private sector organisations, no panacea for an effective and efficient organisation has been found. The analytical framework also provides a means for examining existing organisations and blueprints of future organisations, allowing for conclusions about improvability and the implications of change.
The context -- Efficient and effective organisations — Approaches in organisational economics -- Incentives, knowledge and adaptability -- The research design -- The organisation of trade fair support in Germany -- The organisation of trade fair support in the United Kingdom -- Organisation matters.
Keywords: Economic policy; Economic Policy